Inovasi Strategi Pembelajaran Daring oleh Guru Sekolah Dasar di Kabupaten Bantul - Nashrulloh, Muhammad Iqbal; Ramandhika, Ravi Dwi; Prastowo, Andi (FONDATIA, 2023)
The selection of learning strategies by teachers has a great impact on the implementation of the learning process. However, the implementation of online learning as a result of the Covid-19 pandemic makes teachers have to determine various appropriate strategies for the smooth implementation of learning in the midst of this pandemic. This study aims to explain the innovation of learning strategies by class teachers at SDIT Salsabila 3 Banguntapan Bantul during the implementation of online learning. This research uses qualitative research methods with data collection techniques through interviews. The results of the study showed that an effective strategy in the context of this study was that elementary school teachers carried out online learning using learning videos. Teachers also use various applications such as whatsapp and virtual applications for videocalls such as google meet to deliver learning materials. The use of these various applications must also be followed bythe development of material that is interesting, concise, and easy to understand by students so that the learning objectives and learning completion of students can be achieved optimally. The last important thing that must be done by teachers to maximize the learning process is to establish communication with the guardians of students.